2011
DOI: 10.1007/s00203-011-0753-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and functional characterization of cytochrome P450 monooxygenases from the brown-rot basidiomycete Postia placenta

Abstract: We explored the molecular diversity and functional capabilities of cytochrome P450 monooxygenases (P450s) from the brown-rot basidiomycete Postia placenta. Using bioinformatic and experimental data, we found 250 genes of P450s in the whole genome, including 60 putative allelic variants. Phylogenetic analysis revealed the presence of 42 families, including 18 novel families. Comparative phylogenetic analysis of P450s from P. placenta and the white-rot basidiomycete Phanerochaete chrysosporium suggested that vig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(124 citation statements)
references
References 46 publications
4
117
1
Order By: Relevance
“…2 and Dataset S3). Some cytochrome P450s are likely involved in aromatic hydroxylation reactions required for methoxyhydroquinone biosynthesis, as well as the hydroxylation of lignin fragments preparatory to aromatic ring fission (28).…”
Section: Resultsmentioning
confidence: 99%
“…2 and Dataset S3). Some cytochrome P450s are likely involved in aromatic hydroxylation reactions required for methoxyhydroquinone biosynthesis, as well as the hydroxylation of lignin fragments preparatory to aromatic ring fission (28).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, basidiomycetous P450s have been reported from comparative phylogenetic analyses of P450s in the white-rot basidiomycete Phanerochaete chrysosporium and the brownrot basidiomycete Postia placenta. 16) CYP5027, CYP5350, and CYP5348 are large families in P. placenta but are absent from P. chrysosporium (Table 1). In contrast, the CYP5144 family has been enlarged in P. chrysosporium but not in P. placenta.…”
Section: Overview Of Fungal P450 Diversitymentioning
confidence: 99%
“…To better understand the metabolic diversity of fungi, it is of great importance to exploit the catalytic functions of numerous P450s. [14][15][16][17][18] In addition to the crucial biological roles of P450s, utilization of their catalytic functions is of great interest in the biotechnology sector. [19][20][21][22] Biocatalytic regio-and stereo-specific oxidations by P450s attract much attention in industry because (i) use of biocatalysts allows reduction in the number of tedious steps such as blocking and deblocking that are common in conventional chemical synthesis, (ii) a single product without by-product formation reduces the cost of downstream purification steps, and (iii) enantiomeric mixtures (rather than racemic mixtures) are strictly required in some fields such as the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of Krueger et al [38] indicated that brown-rot fungus Gloeophyllum trabeum might be suitable for the biodegradation of styrene. Although white-rot fungi degrading xenobiotic compounds was originally attributed to its lignin-degrading enzyme system, Ide et al [39] suggested that cytochrome P450 showed a novel catalytic property in xenobiotic metabolism. All annotated enzymes or degradation processes could be found in P. betulinus transcriptome, demonstrating that P. betulinus could not only harbor metabolic xenobiotic materials but also potentially degradation of environmental pollutants.…”
Section: Discussionmentioning
confidence: 99%